The Influence of the Work Environment, Motivation and Human Resources Competency on Employee Performance at the Education, Culture, Youth and Sports Office of Gorontalo Province - Hien Ishak; Ellys Rachman; Amrain Mustafa, (Journal of Economic, Business, and Administration (JEBA), 2021)
This research aims to: 1) find out how the influence of the Work Environment partially on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 2) find out how the influence of the motivation partially on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 3) find out how the influence of the human resources competency partially on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 4) how the Work Environment, Motivation, and Human Resources Competence Simultaneously on Employee Performance in the Education, Culture, Youth and Sports Office of Gorontalo Province.This research uses an explanatory research method; the quantitative method emphasizes objective phenomena and maximizes objectivity. This research design uses numbers, statistics, structure, and controlled experiments, with data collection techniques through observation, interviews, and documentation. A sample of 141 people from a total population of 218 people including the Head of the Education, Culture, Youth and Sports office of Gorontalo Province.The results showed that: 1) partially, the work environment does not have a positive influence on employee performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 2) partially motivation has a positive and simultaneous influence on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 3) partially human resources competencies have a positive and simultaneous influence on employee performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province; 4) simultaneously, the variables of the Work Environment, Motivation, and Competence of Human Resources have a positive effect on Employee Performance in the Education, Culture, Youth, and Sports Office of Gorontalo Province.